VLSI Architectures of Approximate Arithmetic Units Applied to Parallel Sensors Calibration - da Rosa, Morgana Macedo Azevedo; da Costa, Patricia Ucker Leleu; da Costa, Eduardo Antonio Cesar; Soares, Rafael I.; Bampi, Sergio (IEEE transactions on circuits and systems. I, Regular papers, 2024)
Approximate computing maximizes area and energy savings for a trade-off between quality and efficiency. Approximate arithmetic operators have emerged as an efficient alternative to design low-power VLSI circuits. This paper investigates the design of approximate arithmetic operator units used in the calibration procedure for radio astronomy light sensors - the so-called StEFCal (statistically efficient and fast calibration) method. The StEFCal algorithm comprises arithmetic operations like a divider, square-accumulate (SAC), and multiply-accumulate (MAC) units. The StEFCal circuit of this work explores the following arithmetic operators: i) two approximate squarer units from the literature, i.e., radix-4 (AxRSU) and SquASH, ii) two approximate iterative-based Newton-Raphson (NR) and Goldschmidt (GLD) dividers, iii) one approximate parallel prefix adder (AxPPA), and iv) a new approximate radix-4 multiplier (AxRMU), proposed in this work, explored in the StEFCal multiply-accumulate circuit design. The AxRSU utilizes the parameters K1 and K2 to represent the number of exact encoders for squarer-and conventional-partial products, respectively, subsequently replaced with approximate encoders. The same principle applies to AxRMU, where the parameter K indicates the number of exact encoders for conventional-partial products, subsequently exchanged with approximate encoders. We demonstrate the efficiency of StEFCal using the approximate arithmetic operators from the Pareto-optimal front that expresses the area-and power-quality trade-off. The results show that using the AxRSU with K1=4 and K2=6 , AxRMU, and AxPPA with K=16 and NR with one iteration has an MSE equal to 89.98 dB and offers up to 158× energy-savings compared to the exact StEFCal, and up to 25× more energy-savings and 3.33× area-savings compared with our previous work, 440× energy-savings compared to the accurate state-of-the-art, and 258× compared with the approximate state-of-the-art.